Pembuatan Prototype Konveyor Pemilah Sampah Guna Membantu Pekerja Pemilah Sampah - SARNO, SALMA SYI'BUL HUDA; Hendrawan, Aloysius Tommy; Untari, Erny (Universitas Muhammadiyah Sorong, 2024)
Everyday human activities will produce residues, both from the consumption process and the results of activities in the form of waste. Problems in waste handling lead to littering and waste without specifying the type of waste. waste sorting is done in a sitting position and waste transportation is done standing with the same worker. This problem is the current reason for designing a tool that functions in adjusting the work position of the waste separator so that it is not burdensome for workers in carrying out their work. Anthropometric dimensions are used to determine the size of the product to be designed, and anthropometry specifically studies body size including linear dimensions, strength, speed and other aspects of body movement. Thorough testing of the system will include observing the system as it starts from the beginning and moving towards the expected final state, with the aim of ensuring that the entire system operates according to the author's original plan and runs stably. The final results of this study will produce conclusions that can be drawn. as follows The role of this ergonomic conveyor uses an anthropometric approach to accommodate comfortable and safe use. This research produces an ergonomic conveyor tool to help waste sorting workers that can prevent injury or good body position when doing work. In addition, this conveyor tool can make work processes and efficiency in sorting organic and inorganic waste.